If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 37x + 1 = 9(4x + -7) Reorder the terms: 1 + 37x = 9(4x + -7) Reorder the terms: 1 + 37x = 9(-7 + 4x) 1 + 37x = (-7 * 9 + 4x * 9) 1 + 37x = (-63 + 36x) Solving 1 + 37x = -63 + 36x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-36x' to each side of the equation. 1 + 37x + -36x = -63 + 36x + -36x Combine like terms: 37x + -36x = 1x 1 + 1x = -63 + 36x + -36x Combine like terms: 36x + -36x = 0 1 + 1x = -63 + 0 1 + 1x = -63 Add '-1' to each side of the equation. 1 + -1 + 1x = -63 + -1 Combine like terms: 1 + -1 = 0 0 + 1x = -63 + -1 1x = -63 + -1 Combine like terms: -63 + -1 = -64 1x = -64 Divide each side by '1'. x = -64 Simplifying x = -64
| 3x+24=4x+12 | | 3x^2+47+140= | | y=6y+13+8 | | 6b=12 | | 9x^2=486 | | 3=22x | | 15=7d | | 5=8x | | 85=8x | | u/8=0.3 | | 85=87x-6 | | t^2-10t+24=0 | | 85=87x | | -4x-7=31 | | 2x^3-64+3x=54+x+23 | | 23x=9 | | 85=87x-6*x+6 | | 5=87x-6*x+6 | | 2v+11=16 | | a/3/4=9 | | 895=87x-6*x+6 | | 4x+15+2x+5=180 | | 895=87x-6*x | | 5-j=3.3 | | 4x-7=(-2x)+9 | | 120+m-c=360 | | 8-3x=3x-2-8x | | 895=87x-6 | | 7a-13=12 | | 17-(5m+7)=4+2m-15 | | 895=87x | | 17-(5m+7)=4+20-15 |